The Role of Strategic Management in Sustainable Development – Case Study: King Khalid University in Kingdom Saudi Arabia – - AllahGabo, Ehssan Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2021)
This study plan to achieve the knowledge of the role of strategic management in sustainable development, inside universities in King Saudi Arabia by applying example in King Khalid University to co-operate with vision 2030 which aim to enable the strategic management in continuous development in universities. And the problem of the study showing the importance of how to illustrate the interest of the organization in strategic management as an Administrative approach. The questionnaire was distributed random samples about (60) questionnaires among Teaching Staff. (51) questionnaire accepted while (9) questionnaire was rejected because it was unuseful for statistical analysis. The researcher used a statistical approach to measure the stability of the questionnaire. Therefore, the stability shows there was a relationship between strategic management and continuous development at King Khalid University. This relation also maintains a good performance work in Saudi Universities. This study performs an accurate opportunity to illustrate the importance of strategic management in Administrative works to show an idea of continuous work by upgrade awareness level of interest to achieve continuous development approach through which the desired goals of the organization can be achieved and the spread of a culture of sustainable development. To establish an administrative structure that helps to find solutions for sustainable development. Also, the importance of this study stems from the fact that it is an opportunity to explain the importance of strategic management and the goals of its application, especially in business administration, in relation to clarifying the idea of permanent work in pursuit of raising the level of awareness of the importance of development entrepreneurship visions, through the axes of balanced strategic management concepts to achieve sustainable development.